A Study Twacha Sharir W.S.R. To Kitibha Kustha (Psoriasis) - Dr. D. V. Shukla, Dr. Gajendra Gurav, (International Journal of Scientific Research and Management (IJSRM), 2017)
Ayurveda is God’s gift for wellbeing of human kind .Today whole world is looking towards ayurveda as a best therapeutic option for worst skin disorders. Skin is the largest and first site visible organ of body acquiring two square meter of surface area & accounting 16-20% of body weight.1 In Ayurvediya Samhitas skin is described as Twacha  various opinion regarding aboutTwacha  uttapati, Twacha stara & associated disorders are mentioned. In modern era due to changes in life style, food habits, stress & environmental conditions, leads to various skin disorders, among these Kitibha Kustha (Psoriasis) is commonest prevalent in India the prevalence of psoriasis varies from 0.44 to 2.8%, it is twice more common in males compared to females, and most of the patients are in their third or fourth decade at the time of presentation.2 In this study an effort is made to study the anatomical changes occurring in skin layers due to Kitibha kustha and  to specify the exact location of Kitibha kustha (psoriasis) in twacha stara described by Sushrutha.